The Effect of the Traditional Dakon Game on the Intelligence of Children Aged 4–5 Years at KB Ester Sidoasri, Sumbermanjing Wetan (An Experimental Quantitative Study) - Nurpitayani, Dwi; Muntomimah, Siti; Nita, Cicilia Ika Rahayu (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine the effect of the traditional game dakon on the intelligence of children aged 4–5 years at KB Ester Sidoasri, Sumbermanjing Wetan District, before and after being given an intervention in the form of the dakon game. This research employed a quantitative approach with a one-group pretest-posttest experimental design. The subjects of the study were children aged 4–5 years enrolled at KB Ester Sidoasri. The instrument used was an intelligence test administered before (pretest) and after (posttest) the dakon game intervention. The results showed a significant increase in the children’s intelligence levels following the intervention. The game proved effective in stimulating children’s cognitive abilities, such as logical thinking, counting, and decision-making. Therefore, the traditional game dakon can serve as an enjoyable and beneficial learning medium to support the cognitive development of early childhood.